'Technology saves us?’ Malaysian lecturers’ beliefs and readiness towards the application of technology-assisted student-centered learning - Siti Amaliya Mohd Radyi; Azri Bin Usman (UIN Raden Mas Said Surakarta, 2022)
Although studies on technology-assisted student-centered learning (henceforth TA-SCL) is enormously growing in the recent years, few researchers concern on the current state of lecturers’ beliefs and readiness to implement TA-SCL. This study aims to explore Malaysian lecturers’ attitude in terms of beliefs and readiness to carry out TA-SCL approach in university context. A survey design under the procedure of quantitative research was applied to reach the objective. This study involved 207 lecturers teaching at some universities in Kuala Lumpur Malaysia who were selected using purposive sampling technique. The data were collected using a four-point Likert scale online questionnaire, and further analyzed in the forms of descriptive statistics using SPSS program. The results demonstrated that Malaysian lecturers hold a high level of beliefs about the application of TA-SCL in their universities. The finding further revealed that they possessed significant degree of readiness to implement TA-SCL in their teaching activities. These findings leave some implications for the integration of technology for educational purpose, particularly to enhance the efficacy of student-centered learning. This study portrays clear picture of Malaysian lecturers’ current beliefs and readiness towards the TA-SCL, as well as offers fruitful insights for educational stakeholders in Malaysia to begin acknowledge this approach in university learning activities.